The Effectiveness of Problem-Based Learning and Scramble Models in Enhancing Critical Thinking Skills of Fifth Grade Elementary School Students in Integrated Science and Social Studies - Talia, Nadia; Airlanda, Gamaliel Septian (Journal of Innovation and Research in Primary Education, 2025)
This study compares the effectiveness of the Problem-Based Learning (PBL) model and the Scramble learning model in enhancing fifth-grade students’ critical thinking skills in Integrated Science and Social Studies (IPAS) at elementary schools. A quasi-experimental design with a pretest-posttest control group was employed. The sample consisted of 20 students divided into two groups, each taught using the PBL or Scramble model. Data were collected through critical thinking skill tests, classroom observations, and documentation. The results indicate that the PBL model significantly improves students’ critical thinking skills compared to the Scramble model, supported by a Mann-Whitney U test with a significance value of 0.004 (<0.05). The test instrument demonstrated high validity and reliability, with a Cronbach’s Alpha of 0.895. Data analysis confirmed that student-centered learning emphasizing real-world problem solving, as in the PBL model, facilitates active engagement, reflective thinking, and collaboration, thus fostering critical thinking development effectively. In contrast, the Scramble model, which focuses on gamified group competition, is less effective in promoting higher-order cognitive processes. These findings recommend implementing Problem-Based Learning as an effective instructional strategy to develop critical thinking skills early on, particularly in integrated science and social studies education at the elementary level.